High-quality Linac-based Stereotactic Body Radiation Therapy with Flattening Filter Free Beams and Volumetric Modulated Arc Therapy for Low–Intermediate Risk Prostate Cancer. A Mono-institutional Experience with 90 Patients. Issue 12 (December 2016) - D'Agostino, G.; Franzese, C.; De Rose, F.; Franceschini, D.; Comito, T.; Villa, E.; Alongi, F.; Liardo, R.; Tomatis, S.; Navarria, P.; Mancosu, P.; Reggiori, G.; et al.
Abstract: Aims: The aim of this phase II study was to evaluate the efficacy and toxicity of stereotactic body radiotherapy in patients with low or intermediate risk prostate cancer. Materials and methods: Biopsy-confirmed prostate cancer patients were enrolled, provided that they had the following characteristics: initial prostate-specific antigen (PSA) ≤ 20 ng/ml, Gleason Score< 7, International Prostate Symptom Score< 7. The treatment schedule was 35 Gy in five fractions, delivered with volumetric modulated arcs with flattening filter free beams. Toxicity was recorded according to CTCAE criteria v4.0. Biochemical failure was calculated according to the Phoenix definition. The Expanded Prostate Cancer Index Composite questionnaire was used to record health-related quality of life. Results: Between December 2011 and March 2015, 90 patients were enrolled (53 low risk, 37 intermediate risk). The median age was 71 years (range 48–82). In total, 58 (64.5%) of the patients had Gleason Score = 6, the remaining had Gleason Score = 7. The median initial PSA was 6.9 ng/ml (range 2.7–17.0). Acute toxicity was mild, with 32.2 patients presenting grade 1 urinary toxicity and 32.2% of patients presenting grade 2 urinary toxicity, mainly represented by urgency, dysuria and stranguria. Rectal grade 1 toxicity was found in 15.5% of patients, whereas grade 2 toxicity was recorded in 6.6% of patients. Regarding late toxicity, grade 1 proctitis was recorded in 11.1% of patients and grade 1 urinary in 38.8%; only two events of grade 2 urinary toxicity were observed (transient urethral stenosis, resolved by a 24 h catheterisation). At a median follow-up of 27 months (6–62 months) only two intermediate risk patients experienced a biochemical failure. Health-related quality of life revealed a slight worsening in all the domains during treatment, with a return to baseline 3 months after treatment. Conclusions: Stereotactic body radiotherapy delivered using linac-based flattening filter free volumetric modulated arc radiotherapy in low and intermediate risk prostate cancer patients is associated with mild toxicity profiles and good patient-reported quality of life. Highlights: To evaluate the outcome of VMAT SBRT in patients with prostate cancer. 90 patients were included in the study. All patients tolerated treatment. Only mild acute and late toxicity were reported. Quality of life was not affected by the treatment.